On CR-submanifolds of the six-dimensional sphere - M. A. Bashir (International Journal of Mathematics and Mathematical Sciences)
We consider proper CR-submanifolds of the six-dimensional sphere S6. We prove that S6 does not admit compact proper CR-submanifolds with non-negative sectional curvature and integrable holomorphic distribution.